Wnt Signaling and Its Significance Within the Tumor Microenvironment: Novel Therapeutic Insights - Patel, Sonal; Alam, Aftab; Pant, Richa; Chattopadhyay, Samit (Frontiers in Immunology, 2019)
Wnt signaling is one of the central mechanisms regulating tissue morphogenesis during embryogenesis and repair. The pivot of this signaling cascade is the Wnt ligand which binds to receptors belonging to Frizzled family or ROR1/ROR2 and RYK family. This interaction governs the downstream signaling cascade (canonical/non-canonical) ultimately extending its effect on cellular cytoskeleton, transcriptional control of proliferation and differentiation and organelle dynamics. Anomalous Wnt signaling has been associated with several cancers, most prominently colorectal, breast, lung, oral, cervical and hematopoietic malignancies. It extends its effect on tumorigenesis by modulating the tumor microenvironment via fine-crosstalk between transformed cells and infiltrating immune cells like leukocytes. This review is an attempt to highlight the latest developments in the understanding of Wnt signaling in the context of tumors and their microenvironment. A dynamic process known as immunoediting governs the fate of tumor progression based on correlation of various signalling pathways in the tumor microenvironment and immune cells. Cancer cells also undergo a series of mutations in the tumor suppressor genes which favours tumorigenesis. Wnt signaling and its crosstalk with various immune cells has both negative as well as positive effects on tumor progression. On one hand, it helps in the maintenance and renewal of the leucocytes whereas on the other hand, it promotes immune tolerance limiting the antitumor response. Wnt signaling also plays a role in epithelial-mesenchymal transition (EMT), thereby promoting Cancer Stem Cells (CSCs) maintenance. Further, we summarize the ongoing strategies used to target aberrant Wnt signaling as a novel therapeutic intervention to combat various cancers and their limitations.